2005
DOI: 10.1002/ajmg.a.30569
|View full text |Cite
|
Sign up to set email alerts
|

Gonadoblastoma in Turner syndrome and Y‐chromosome‐derived material

Abstract: The identification of Y-chromosome material is important in females with Ullrich-Turner syndrome (UTS) due to the risk of developing gonadoblastoma or other gonadal tumors. There is controversy regarding the frequency of the Y-chromosome-derived material and the occurrence of gonadoblastoma in these patients. The aim of our study was to evaluate a large number of patients with UTS, followed before and during the pubertal age for the prevalence of Y-chromosome derived material, the occurrence of gonadoblastoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
12

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 43 publications
8
62
0
12
Order By: Relevance
“…25 Although the frequency of gonadoblastoma in Turner syndrome with occult Y chromosome mosaicism without evidence of virilization is not fully appreciated, additional studies are recommended in these cases to help prevent a potential life-threatening cancer. 32 FISH with X and Y centromere probes should be performed on a minimum of 200 interphase cells. An appropriate database should be created and normal cutoff values should be established for a Y chromosome signal using normal female controls.…”
Section: Postnatal Studiesmentioning
confidence: 99%
“…25 Although the frequency of gonadoblastoma in Turner syndrome with occult Y chromosome mosaicism without evidence of virilization is not fully appreciated, additional studies are recommended in these cases to help prevent a potential life-threatening cancer. 32 FISH with X and Y centromere probes should be performed on a minimum of 200 interphase cells. An appropriate database should be created and normal cutoff values should be established for a Y chromosome signal using normal female controls.…”
Section: Postnatal Studiesmentioning
confidence: 99%
“…Patients with TS, in particular those with 45,X or a marker chromosome at conventional cytogenetic analysis, may benefit from molecular screening analysis to detect the presence of Y-chromosome material (98,99). An unselected series of 171 patients with TS diagnosed cytogenetically was studied for Y-chromosome markers (SRY and Y-centromeric DYZ3 repeats).…”
Section: Y-chromosome Mosaicismmentioning
confidence: 99%
“…Of the 14 patients, 12 were gonadectomised and in four (33%) gonadoblastoma was detected under 16 years of age. According to the authors, the epidemiological studies in the past underestimated the risk of gonadal neoplasms in this group of patients (98). A different study confirmed the association of Y fragments with gonadoblastoma at an early age; however, the presence of Y material was not combined with virilisation (99).…”
Section: Y-chromosome Mosaicismmentioning
confidence: 99%
“…However, recent epidemiological studies have questioned the postulated high incidence of gonadoblastoma in these cases (7) .…”
Section: Turner Syndrome and Gonadal Tumorsmentioning
confidence: 99%
“…This risk has previously been estimated to be almost 30%, and it is directly proportional to age, being significantly higher after puberty due to a lower degree of virilization of the external genitalia and to the intraabdominal localization of the gonad (7) . Gonadectomy is generally recommended; however, this consensus is questioned by some recent studies.…”
Section: Clinical-genetic Investigation Protocolmentioning
confidence: 99%